2017
DOI: 10.1002/adfm.201700243
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Oxygen Diffusion and Electronic Conduction in SrTiO3 by Dislocation‐Induced Space Charge Fields

Abstract: Plastic strain engineering was applied to induce controllable changes in electronic and oxygen ion conductivity in oxides by orders of magnitude, without changing their nominal composition. By using SrTiO 3 as a model system of technological importance, and by combining electrical and chemical tracer diffusion experiments with computational modeling, it is revealed that dislocations alter the equilibrium concentration and distribution of electronic and ionic defects. The easier reducibility of the dislocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 75 publications
(119 reference statements)
2
94
0
1
Order By: Relevance
“…In ferroelectrics, theoretical work has suggested that dislocations can pin domain walls and, hence, should be able to influence dielectric losses for high‐power applications . The applicability of the 1‐dimensional doping concept, however, hinges on availability of single crystals, which can be deformed . Dislocations on a small scale can be introduced by indentation or surface treatments, but with these methods macroscopical changes in the ferroelectric properties cannot be reached.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In ferroelectrics, theoretical work has suggested that dislocations can pin domain walls and, hence, should be able to influence dielectric losses for high‐power applications . The applicability of the 1‐dimensional doping concept, however, hinges on availability of single crystals, which can be deformed . Dislocations on a small scale can be introduced by indentation or surface treatments, but with these methods macroscopical changes in the ferroelectric properties cannot be reached.…”
Section: Introductionmentioning
confidence: 99%
“…7 This approach has demonstrated large changes in conductivity in plastically deformed TiO 2 and SrTiO 3 single crystals. [8][9][10] Similarly, dislocations have been proven to pin flux lines in superconductors 11 and to enhance the thermoelectric figure of merit by reducing thermal conductivity. 12 In ferroelectrics, theoretical work has suggested that dislocations can pin domain walls 13 and, hence, should be able to influence dielectric losses for highpower applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that electrical conductivity can be modified by structural changes originating from the formation of dislocation [28,29,37,38], grain boundaries [10,21], surfaces [54], and interfaces [22][23][24]. The common observation in the modified electrical conductivity was the presence of oxygen vacancies.…”
Section: Oxidation State Change Of Ce Ions In the Deformed Areamentioning
confidence: 99%
“…In TiO 2 (Figure 9) or SrTiO 3 the dislocations showed (apart from the sign) similar space charge effects. [33,34] As long as the spacing of the dislocation lines are pronounced, the overall conductivity effects are only perceptible if one measures along the onedimensional objects and as long as they are highly conducting. In all other cases the bulk effects dominate.…”
Section: ••mentioning
confidence: 99%